1995
DOI: 10.2337/diab.44.6.626
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-Like Peptide I Reduces Postprandial Glycemic Excursions in IDDM

Abstract: Effects of human glucagon-like peptide I (GLP-I)(7-36)amide were examined in volunteers having insulin-dependent diabetes mellitus (IDDM) with residual C-peptide (CP) secretion (n = 8, 7 men and 1 woman; age, 31 +/- 1.4 years; body mass index, 24.7 +/- 0.7 kg/m2; duration of diabetes, 3.2 +/- 0.8 years; insulin dose, 0.41 +/- 0.05 U.kg-1.day-1; meal-stimulated CP, 1.0 +/- 0.2 nmol/l [means +/- SE]). After a mixed meal (Sustacal, 30 kJ/kg body wt), intravenous injection of GLP-I, 1.2 pmol.kg-1.min-1 through 120… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0
2

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(44 citation statements)
references
References 11 publications
1
41
0
2
Order By: Relevance
“…This action of the hormone reduces hepatic glucose output and may explain, at least in part, an ability of GLP-1 to lower levels of blood glucose in type 1 (juvenile-onset) diabetic subjects [11,36]. Interestingly, the ability of GLP-1 to suppress pancreatic glucagon secretion also appears to be glucose-dependent.…”
Section: B Glp-1 As a Blood Glucose-lowering Agentmentioning
confidence: 99%
“…This action of the hormone reduces hepatic glucose output and may explain, at least in part, an ability of GLP-1 to lower levels of blood glucose in type 1 (juvenile-onset) diabetic subjects [11,36]. Interestingly, the ability of GLP-1 to suppress pancreatic glucagon secretion also appears to be glucose-dependent.…”
Section: B Glp-1 As a Blood Glucose-lowering Agentmentioning
confidence: 99%
“…16 While in humans, the glucose-lowering actions are likely mediated largely through delayed gastric emptying, there is additional evidence that inhibition of glucagon secretion may also play a role. 17 In animal models of type-1 diabetes, administration of GLP-1-receptor agonists has been shown to improve glycemia, in part due to increases in beta-cell mass. 5,18,19 Native GLP-1, as well as currently available GLP-1-receptor agonists, have short biological half-lives.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacokinetics studies have revealed that SQV possesses very low oral bioavailability in the range of 4-16% of administered dose (Dupre et al, 1995;Schapiro et al, 1996). Recent investigations have demonstrated that all protease inhibitor (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports speculate that low and variable oral bioavailability of SQV and other protease inhibitors is primarily caused by membrane bound efflux proteins like Pglycoprotein and multi drug resistance proteins (MRPs) and partly due to CYP3A4 mediated metabolism (Dupre et al, 1995;Fitzsimmons and Collins, 1997;Kim et al, 1998;Polli et al, 1999;Williams et al, 2002). Presence of P-gp on blood brain barrier further limits the entry of these drugs into the brain making it a sanctuary site for viral replication (Bachmeier et al, 2005).…”
Section: Introductionmentioning
confidence: 99%